THE PERCEPTIONS OF GMNI BANYUWANGI MEMBERS TOWARD SUKARNO’S THOUGHT ON SARINAH: WOMEN’S CONTRIBUTIONS TO THE STUGGLE OF THE REPUBLIC OF INDONESIA. - sherlynda puspita sari; Sahru Romadloni; I Kadek Yudiana (SOSIOEDUKASI, 2026)
This study aims to describe the perceptions of GMNI Banyuwangi members regarding Sukarno’s views on women’s contributions to the struggle for the Republic of Indonesia. Data collection was conducted through literature review, interviews, observation, and documentation. In-depth interviews were conducted with 11 informants selected through purposive sampling, consisting of the chairperson of the Banyuwangi GMNI DPC, the deputy head of the Sarinah division of the Banyuwangi GMNI DPC, the political bureau of the Banyuwangi GMNI DPC, the cadre development bureau of the DPK KIP, the deputy head of the DPK KIP, a member of the DPK Engineering, the chairperson of the DPK ISIP, a member of the DPK Law, the secretary of the DPK FPP, and the deputy head of the political division of the DPK FPP. These interviews were conducted to explore the informants’ subjective interpretations of Sukarno’s thoughts on Sarinah and women’s contributions to the struggle for the Republic of Indonesia. Observations were conducted to examine organizational dynamics and patterns of cadre interaction during Sarinah discussion activities. Documentation included archives and internal GMNI documents. The research findings indicate that the majority of GMNI Banyuwangi members view women as an essential element of the struggle, equal to men, likened to two flapping wings that mutually support one another. The depth of understanding regarding Sukarno’s thoughts on Sarinah remains varied, influenced by the limited critical reading skills of GMNI Banyuwangi members. Sukarno is perceived as a revolutionary thinker who demanded full women’s participation to achieve comprehensive independence. In general, these findings indicate a gap between Sukarno’s normative ideas and organizational practices, making the strengthening of gender-sensitive leadership development essential to actualizing Sarinah’s values and enriching today’s nationalist student movement.